Effect of Codon Optimisation on the Production of Recombinant Fish Growth Hormone in Pichia pastoris - Hussin A. Rothan; Teh Ser Huy; Zulqarnain Mohamed (The Scientific World Journal)
This study was established to test the hypothesis of whether the codon optimization of fish growth hormone gene (FGH) based on P. pastoris preferred codon will improve the quantity of secreted rFGH in culture supernatant that can directly be used as fish feed supplements. The optimized FGH coding sequence (oFGH) and native sequence (nFGH) of giant grouper fish (Epinephelus lanceolatus) were cloned into P. pastoris expression vector (pPICZαA) downstream of alcohol oxidase gene (AOX1) for efficient induction of extracellular rFGH by adding 1% of absolute methanol. The results showed that recombinant P. pastoris was able to produce 2.80±0.27 mg of oFGH compared to 1.75±0.25 of nFGH in one litre of culture supernatant. The total body weight of tiger grouper fingerlings fed with oFGH increased significantly at third (P<0.05) and fourth weeks (P<0.01) of four-week experiment period compared to those fed with nFGH. Both oFGH and nFGH significantly enhanced the final biomass and fish survival percentage. In conclusion, codon optimization of FGH fragment was useful to increase rFGH quantity in the culture supernatant of P. pastoris that can be directly used as fish feed supplements. Further studies are still required for large scale production of rFGH and practical application in aquaculture production.